Identification of a novel cardiac epitope triggering T-cell responses in patients with myocardial infarction. (December 2022) - Hapke, Nils; Heinrichs, Margarete; Ashour, DiyaaElDin; Vogel, Elena; Hofmann, Ulrich; Frantz, Stefan; Campos Ramos, Gustavo
Abstract: T-cells contribute to pathophysiological processes in myocardial diseases, including myocardial infarction (MI) and heart failure (HF). Antigen-specificity is a hallmark of T-cell responses but the cardiac antigens that trigger heart-directed T-cell responses in patients have not yet been uncovered, thus posing a roadblock to translation. In the present exploratory study, we identified a peptide fragment of the beta-1 adrenergic receptor (ADRB1) that elicits CD4 + T-cell responses after myocardial infarction in patients with a defined HLA haplotype. Our observations may advance the development of tools to monitor other antigen-specific immune responses in patients. Graphical abstract: Unlabelled Image Highlights: The beta-1 adrenergic receptor (ADRB1) is an autoantigen source in MI patients. ADRB1167 – 182 triggers T-cell responses in HLA-DRB1*13 + MI patients. Cardiac epitope mapping may provide new tools to monitor post-MI T-cell responses. Further studies are needed to uncover the relevance of ADRB1− specific T-cells in MI.